Meet the parents: Normative emotions in Finnish wolf politics - Hiedanpää, Juha; Pellikka, Jani; Ojalammi, Sanna (Finnish Society for Human-Animal Studies (YKES ry), 2016)
The reappearance of the grey wolf (Canis lupus) in 2005 after a one-hundred-year absence surprised rural communities in Southwest Finland. Various social emotions emerged and began to shape how people thought about wolves and reoriented their daily practices. In this paper, we examine how emotional reactions and actions functioned in the presence of the wolf and the non-intervention wolf policy until 2014. We used written documents, interviews and focus group discussions as our primary materials. Our results indicate how normative emotions have played a role in influencing Finnish wolf policy.